CTCF shapes chromatin structure and gene expression in health and disease. (22nd August 2022) - Dehingia, Bondita; Milewska, Małgorzata; Janowski, Marcin; Pękowska, Aleksandra
Abstract: CCCTC‐binding factor (CTCF) is an eleven zinc finger (ZF), multivalent transcriptional regulator, that recognizes numerous motifs thanks to the deployment of distinct combinations of its ZFs. The great majority of the ~50, 000 genomic locations bound by the CTCF protein in a given cell type is intergenic, and a fraction of these sites overlaps with transcriptional enhancers. Furthermore, a proportion of the regions bound by CTCF intersect genes and promoters. This suggests multiple ways in which CTCF may impact gene expression. At promoters, CTCF can directly affect transcription. At more distal sites, CTCF may orchestrate interactions between regulatory elements and help separate eu‐ and heterochromatic areas in the genome, exerting a chromatin barrier function. In this review, we outline how CTCF contributes to the regulation of the three‐dimensional structure of chromatin and the formation of chromatin domains. We discuss how CTCF binding and architectural functions are regulated. We examine the literature implicating CTCF in controlling gene expression in development and disease both by acting as an insulator and a factor facilitating regulatory elements to efficiently interact with each other in the nuclear space. Abstract : This review discusses how CTCF shapes the 3D chromatin structure and chromatin domains, how CTCF binding and architectural functions are regulated, and how CTCF controls gene expression in development and disease by acting as an insulator and a facilitator for regulatory element interaction in the nuclear space.